Muhibbin Sebagai Representasi Budaya Pop Santri di Banyumas - Ahmad Yusuf Prasetiawan; Lis Safitri (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
The purpose of this paper is to provide a description of the emergence and rise of pop culture and the phenomenon of the Muhibbin which became a wave among students. Pop culture usually only lives in modern, urbanistic society, whereas Islamic boarding schools are known as Islamic education institutions that are generally traditionalist, closed, and conventional. As the pesantren metamorphic wave with many formal schools has sprung up since the 2000s, the pesantren’s contact with the outside world has become more intense, the influences of giving color, and new streams, especially in this social media culture, indications of the emergence of pop culture have strengthened. This study is a cross method or method combination of quantitative and qualitative, using participatory heuristic techniques (observation, interview, documentation), verification, and interpretation in digging data. This is sectional research or in a limited period (January-June 2019). Determination of informants using random sampling techniques, from 183 Islamic boarding schools listed in the Ministry of Religion Banyumas Regency, 31 boarding schools were taken, with each of the 3-4 students, bringing the total to 100 respondents. The results showed that the relationship between the santri community and pop culture was not new since the religious songs industry was booming, but with the emergence of the Muhibbin trend (lovers of the Apostles with sholawat songs), the santri community found the right form of contradictory relations between orthodoxy students with trendy pop, because Santri is the object and the subject at the same time. Muhibbin wave embodies a compromise between Santri’s sacred Islamic values and pop expression as a young spirit, where the age of santri in general. Tujuan penulisan ini adalah untuk memberikan deskripsi tentang kemunculan dan maraknya budaya pop di kalangan santri dan fenomena Muhibbin yang menjadi wave. Budaya pop biasanya hanya hidup dalam masyarakat modern yang urbanistik, sedangkan Pesantren dikenal sebagai lembaga pendidikan Islam yang umumnya tradisionalis, tertutup dan konvensional. Seiring gelombang metamorfosa Pesantren dengan sekolah formal yang banyak bermunculan sejak tahun 2000-an, persentuhan Pesantren dengan dunia luar kian intens, pengaruh masuk memberi warna, dan arus baru (newmainstream), terlebih dalam budaya sosial media ini, Indikasi munculnya pop culture pun menguat. Penelitian ini merupakan cross methode atau metode kombinasi antara kuantitatif dan kualitatif, mengggunakan teknik heuristik partisipatoris (observasi, wawancara, dokumentasi), verifikasi, serta interpretasi dalam menggali data. Penelitian bersifat sectional research atau dalam kurun waktu terbatas (Januari-Juni 2019). Penentuan informan menggunakan teknik random sampling, dari 183 Pesantren yang terdaftar pada Dipontren Kantor Kementerian Agama Kabupaten Banyumas, diambil 31 Pesantren, dengan masing-masing 3-4 santri, sehingga total menjadi 100 responden. Hasil penelitian menunjukkan persentuhan komunitas santri dengan budaya pop bukanlah hal baru, telah terjadi sejak industri lagu-lagu religius booming, tetapi dengan munculnya trend Muhibbin (pecinta Rasul dengan lagu-lagu sholawat), komunitas santri menemukan bentuk yang tepat dari relasi yang kontradiktif antara ortodoksi santri dengan pop yang trendy, karena Santri menjadi objek dan subjeknya sekaligus. Muhibbin wave mewujudkani sebuah kompromi antara nilai keislaman Santri yang sakral dengan ekspresi pop sebagai semangat muda, dimana usia santri pada umumnya.